The dilemmas of globalisation vs. The ethics of right-minded thinking: an outline of the problem - Dura, Adam A. (Folia Philosophica, 2003)
The article deals with the anthropological and ethical aspect of one of the most urgent contemporary problems i.e. globalisation and planetary society. Through the course of analysis the author presents the selected dilemmas of globalisation and then forms a statement that according to the ethics of the right-minded thinking it is theoretically possible to reduce the ambivalence of the above-mentioned processes. Human life is important in ‘here-now-being’ and no human being can put off indefinitely resolving his or her acute problems, including the possibility of experiencing happiness. Such a possibility has been presented here in the context of the ethical postulate of the protection of the spheres of privacy and intimacy, irrespective of other macro scale activities. Although the above is not the only or sufficient level of activity, nevertheless it is valuable being ready for use almost right away, a recentiori. What is also necessary are the solutions on a macro-ethical scale. Recentivism itself offers new possibilities like recentivist philosophy of history which leads to the postulate of creating the optimal social prognoses based on properly formulated directive of historicism, and in keeping with the principle of recentivism: whatever is, is now.